The Sustainable Production of Terpenoids in Cyanobacterial Chassis - Bo Hong; Ling Qiu; Ruo Lv; Zongxia Yu (Microorganisms, 2025)
Terpenoids, which are widely distributed in nature, possess diverse biological activities, physiological functions, and economic values. They are extensively exploited by plants and microorganisms. However, the abundance of terpenoids in natural hosts is extremely low, making it difficult to meet the market demands. In recent years, along with the advancement of metabolic engineering and synthetic biology, it has become feasible for microorganisms to produce exogenous terpenoids sustainably. Cyanobacteria and other photosynthetic microorganisms have attracted growing attention due to their capacity to produce terpenoids by harnessing light and carbon dioxide. In this article, we comprehensively summarize the biosynthetic pathways of terpenoids and the progress in utilizing cyanobacteria as chassis for the production of terpenoids, and further discuss strategies for augmenting the yields of terpenoids.